Does the repeat dose of gonadotropin-releasing hormone agonist trigger in polycystic ovarian syndrome improve in vitro fertilization cycles outcome? A clinical trial study - Abbas Aflatoonian; Fatemeh Haghighi; Masrooreh Hoseini; Saeid Haghdani (Shahid Sadoughi University of Medical Sciences, 2020)
Background: A repeat dose of Gonadotropin-releasing Hormone (GnRH) agonist could provide long duration of luteinizing hormone (LH) surge and amplitude appropriately. Objective: Improvement in oocyte maturity could be obtained by a repeat dose of GnRH agonist. Materials and Methods: In this randomized double-blinded study, 120 women with polycystic ovarian syndrome and serum estradiol level (E2) > 3000 who were candidate for in vitro fertilization with Antagonist protocol were enrolled between July 2018 and July 2019. Participants were randomized in two groups - and final oocyte maturation was triggered with two doses: In group A, a repeat dose of 0.1 mg, 12 hr. after the first dose and in group B, 0.2 mg SC triptorelin (decapeptyl) 35 hr. prior to oocyte retrieval. Serum Estradiol, LH, and progesterone concentration were measured on the trigger day. Serum LH measurement was done three times in both groups. The outcomes were oocyte yield, meiosis (M) I, MII, Maturity rate, germinal vesicle (GV) rate, 2 pronuclear, embryo yield, ovarian hyper stimulation syndrome rates. Results: Maturity rate (p = 0.89), MI (p = 0.38), MII (p = 0.89), and GV oocytes (p = 0.38) were not statistically different between the two study groups. LH levels measured at 12 hr post-trigger did not relate statistically significant with maturity rate in our participants (p = 0.96). No empty follicular syndrome was reported. Conclusion: Although, the second dose of GnRH agonist after 12 hr since the first dose could provide duration of LH surge and amplitude and as a result no empty follicular syndrome was seen, the maturity rate, MI, MII, and GV oocytes were not different between the two study groups.